Unpacking the 'black box' of scanning probe microscopes for the next generation.
Scanning probe microscope (SPM) techniques have evolved beyond imaging and manipulation with single atom resolution, to the sub-molecular and sub-atomic level. Yet, this success can jeopardise real process understanding, and so the EU-funded ACRITAS project set out to redress the balance.